2015
DOI: 10.1016/j.appet.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical differences in children with autism spectrum disorder with and without food selectivity

Abstract: A B S T R A C TSeveral studies have described the atypical eating behaviors frequently occurring in children with autism spectrum disorder (ASD), and food selectivity is the most frequent of these problems. The everyday management of mealtime behaviors among children with ASD can have a negative impact on family routines and become a significant stressor for families. However, much remains unknown about why food selectivity is so prevalent among individuals with ASD. The objective of this study was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 50 publications
3
67
1
16
Order By: Relevance
“…Among a wide range of atypical behaviors, children with ASD often have atypical feeding behaviors, of which food selectivity is the most common [4][5][6]. For the most part, even autistic children with food selectivity achieve growth adequacy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Among a wide range of atypical behaviors, children with ASD often have atypical feeding behaviors, of which food selectivity is the most common [4][5][6]. For the most part, even autistic children with food selectivity achieve growth adequacy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 138 (cohort of patients treated over a six6 year period), 42 (30%) had an ASD (Esan, Chester, Gunaratna, Hoare, & Alexander, 2015). However, it is important to point out here that a number of studies and papers have highlighted the relatively high rate of intellectual disabilities in both children and adults with ASD in the general population/community samples (e.g., La Malfa, Lassi, Bertelli, Salvini, & Placidi, 2004;Matson & Shoemaker, 2009;Postorino, Fatta, Sanges, Giovagnoli, De Peppo, Vicari, & Mazzone, 2016;Tonnsen, Boan, Bradley, Charles, Cohen, & Carpenter, 2016). with ASD exhibited a significantly higher total AQ scores compared to those without a diagnosis of ASD.…”
Section: Prevalence Of Asd In Secure Psychiatric Hospitalsmentioning
confidence: 99%
“…The majority of these studies main research focus, however, was examining the epidemiology of ASD rather than specifically investigating the rate of comorbidity of ID in individuals with ASD (Postorino, Fatta, Sanges, Giovagnoli, De Peppo, Vicari, & Mazzone, 2016). Despite the well-established high co-morbidity between ID and ASD, the present paper focuses on studies which specifically look at individuals with ASD because there has been relatively little research investigating ASD in the criminal justice system.…”
Section: Rates Of Overlap Between Intellectual Disability and Asdmentioning
confidence: 99%
“…Research has shown that it is more common for children with ASD to display food selectivity challenges compared to children who are typically developing Johnson et al, 2008;Postorino, et al, 2015;Schreck, Williams, & Smith, 2004;Suarez et al, 2014). Cermak, Curtin, and Bandini (2010) conducted a review of the literature on sensory sensitivity in children with ASD and how this may impact food selectivity in this population.…”
Section: (American Occupational Therapy Associationmentioning
confidence: 99%
“…Mealtime difficulties for children with ASD included refusal to eat; food selectivity, such as eating limited types or amounts of foods; and difficult behaviors affecting mealtime Johnson, Handen, Mayer-Costa, & Sacco, 2008;Koegel et al, 2012;Nadon et al, 2011;Postorino et al, 2015;Suarez et al, 2014).…”
Section: (American Occupational Therapy Associationmentioning
confidence: 99%